Ion Transport in Solvated Sodium-Ion Conducting Gel Polymer Electrolytes - Kuray, Preeya; Mei, Wenwen; Sheffield, Sarah E.; Sengeh, Joseph; Pulido, Carlos Rolando Fernandez; Capparelli, Clara; Hickey, Robert J.; Hickner, Michael A. (Frontiers in Energy Research, 2020)
Single ion conducting gel polymer electrolytes (GPEs) are characterized as having a certain amount of ionic liquid or solvent incorporated into a single ion-conducting polymer matrix and may afford the advantages of high conductivity and low electrolyte polarization under battery operation. Single ion conducting polymers often suffer from low conductivity due to their reliance on polymer segmental motion to achieve sufficient ion mobility. However, by incorporating specific solvents into a single ion conducting matrix, mobility of the polymer can be enhanced while still maintaining the advantages of single ion conduction. Although many of the solvents used to swell GPEs are mixtures of flammable organic solvents (such as dimethyl carbonate), there are many potential non-reactive, low vapor pressure solvents that could effectively solvate alkali-ion based GPEs and plasticize the polymer matrix to enhance ion conductivity. Adipate-based solvents are a group of non-volatile plasticizers with low viscosities and low vapor pressures at room temperature derived from adipic acid. The ester groups in these solvents may effectively solvate alkali ions such as Na+, leading to higher conductivity, while circumventing issues of flammability found in current alkali-ion conducting electrolytes. This study investigates the properties of sodium-ion conducting GPEs that have been swollen with varying adipate-based solvents and the subsequent dielectric response from the solvent addition. Dielectric relaxation spectroscopy was used to characterize the Na+ conductivity, static dielectric constant, ion-conducting content, and mobility of the membranes before and after the non-volatile solvent uptake. Understanding this relationship will pave the path toward safer, more efficient solid-state polymer electrolytes for battery applications.